Adsorptive removal of reactive violet 5 azodye (V5R) with biochar: An ecofriendly technology - Samuel Kofi Tulashie; Mustapha Iddrisu; Stephen Mensah; Francis Kotoka; Kofi Adu (Sustainable Chemistry for the Environment, 2023)
Industrial effluent comprising reactive violet 5 azodye (V5R) discharged into clean water bodies induces adverse health hazards on our ecosystem and throughout our food chain. This study investigates the adsorption capacity of biochar derived from bamboo stem (B500) and calabash (C500), respectively. The biochar samples were prepared by pyrolysis at 500 ℃ and characterized by FT-IR, SEM, and the nitrogen (N2) adsorption-desorption isotherm. The BET specific surface areas of the B500 and C500 were measured to be 174. 67 and 44.78 m2/g, respectively. The biochar samples were found to be mesoporous, with mean pore diameters of 21.1 and 26.5 nm for B500 and C500, respectively. Overall, the B500 sample exhibited better adsorption capacity than C500 towards the removal of V5R dye species at both the 0.02 and 0.36 g doses examined. According to kinetic studies, the adsorption process followed the pseudo-second order kinetics. Further, the isotherm studies revealed that the V5R dye adsorption followed the Langmuir adsorption model. The proposed mechanism of adsorption is either by hydrogen bonding, π-π stacking interactions of the aromatic groups, or surface coordination. The study shows that the adsorbent dose has a significant influence on adsorption capacity since adsorbent dose of 0.02 showed higher adsorption capacity than the 0.36 g dose. The equilibrium adsorption capacity of 15.083 and 0.016 mg/g at Co = 50 mg/L and adsorbent dose of 0.02 g was obtained for B500 and C500 biochar, respectively.